Paraptosis and NF-κB activation are associated with protopanaxadiol-induced cancer chemoprevention - Wang Chong-Zhi; Li Binghui; Wen Xiao-Dong; Zhang Zhiyu; Yu Chunhao; Calway Tyler D; He Tong-Chuan; Du Wei; Yuan Chun-Su (BMC, 2013)
Abstract Background Protopanaxadiol (PPD) is a triterpenoid that can be prepared from steamed ginseng. PPD possesses anticancer potential via caspase-dependent apoptosis. Whether paraptosis, a type of the caspase-independent cell death, is also induced by PPD has not been evaluated. Methods Cell death, the cell cycle and intracellular reactive oxygen species (ROS) were analyzed by flow cytometry after staining with annexin V/PI, PI/RNase or H2DCFDA. We observed morphological changes by crystal violet staining assay. Mitochondrial swelling was measured by ultraviolet-visible spectrophotometry. The activation of NF-κB was measured by luciferase reporter assay. Results At comparable concentrations of 5-fluorouracil, PPD induced more cell death in human colorectal cancer cell lines HCT-116 and SW-480. We demonstrated that PPD induced paraptosis in these cancer cells. PPD treatment significantly increased the percentage of cancer cells with cytoplasmic vacuoles. After the cells were treated with PPD and cycloheximides, cytoplasmic vacuole generation was inhibited. The paraptotic induction effect of PPD was also supported by the results of the mitochondrial swelling assay. PPD induced ROS production in cancer cells, which activated the NF-κB pathway. Blockage of ROS by NAC or PS-1145 inhibited the activation of NF-κB signaling. Conclusions PPD induces colorectal cancer cell death in part by induction of paraptosis. The anticancer activity of PPD may be enhanced by antioxidants such as green tea, which also inhibit the activation of NF-κB signaling.